The CLIMATE CHANGE IMPACT ON THE HUMAN RIGHT TO ENVIRONMENTAL CONDITIONS OF A SPECIFIED QUALITY (SAFE, CLEAN, HEALTHY AND SUSTAINABLE ENVIRONMENT): SOME INTERNATIONAL ENVIRONMENTAL LAW ISSUES - Sushyk, Olha; Shompol, Olena (Review of European and Comparative Law, 2019)
This article discusses recognition between climate change and human rights at the international level. The analysis shows that despite the UN climate change framework does not adequately address the magnitude of the threat posed by climate change related harm to human rights, domestic, regional or international courts must take account of its provisions in deciding cases. The article argues that the causes for climate cases are diverse, whereby the most often ones are those referring to the competent public authority’s failure to fulﬁl its obligation to regulate limitations of the greenhouse gas (GHG) emissions. Further identify the links between human rights and environmental protection, were apparent at least from the first international conference on the human environment, held in Stockholm in 1972. More broadly, it demonstrates international environmental agreements, were some aspects of the right to environmental conditions of a specified quality are identify. This article discusses also theoretical issues of individual environmental rights and the right to environmental safety in Ukraine. Keywords: climate, human rights, environmental, Ukraine